The Role of an Advocate as a Mediator In Medical Dispute Resolution - Fahmi Syaifuddin Ramdhany; Gandhi Pramudhita (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2019)
Mediation is an alternative with the resolution of disputes that be a way out in doing with the resolution of disputes which is considered very simple, process fast and low cost, but a mediation process were considered to eye better than the hospitals or the patients and law enforcement. As mandated in number 39 2009 article 29 who explained that “in terms of health workers is suspected of committing an omission in run profession, the negligence would have to be settled first through mediation“, the mediation can be carried out in the court or litigation or outside a court or non-litigation of the court. The importance of a mediation process are needed someone who competent on legal affairs who has committed training a mediator and have passed in an exam held by the agency of education accredited the supreme court and have made an education focusing on the science of law health. The figure of an advocate who have passed training a mediator and had embarked on mastering education of law focusing on the science of law health is necessary in settling medical disputes.